The Role of Economic Development and Perceived Growth Opportunities in Employee Reactions to M&As: A Study of the Merger Syndrome Across 29 Countries. (April 2017) - Paustian-Underdahl, Samantha C.; Fainshmidt, Stav; Sanchez, Juan I.; Misati, Everlyne; Zhao, Yue; Zhang, Haiyan
We draw on the economic institutions literature and on transactional stress theory to explain differences in employee reactions to mergers and acquisitions (M&As) across 29 nations. Using a sample of 10, 803 middle managers and executives, we find that country-level economic development moderates the effects of an M&A on employee attitudes and outcomes. Unlike in more advanced economies where M&As are associated with a reduction in perceived growth opportunities among employees, in less advanced economies, M&As are associated with increased perceptions of growth opportunities. These perceived growth opportunities post-M&A are associated with positive employee outcomes such as work–life balance, job satisfaction, organizational satisfaction, and reduced turnover intentions. Our results highlight the role that growth opportunities and the economic context play in harnessing human capital after an M&A.